Carbon nanotube-based multi electrode arrays for neuronal interfacing: progress and prospects - Hanein, Yael; Bareket-Keren, Lilach (Frontiers in Neural Circuits, 2013)
Carbon nanotube coatings have been demonstrated over the past several years as a promising material for neuronal interfacing applications. In particular, in the realm of neuronal implants, carbon nanotubes have major advantages owing to their unique mechanical and electrical properties. Here we review recent investigations utilizing carbon nanotubes in neuro-interfacing applications. Cell adhesion, neuronal engineering and multi electrode recordings with carbon nanotubes are described. We also highlight prospective advances in this field, in particular, progress towards flexible, bio-compatible carbon nanotubes technology.